In The Blink of an Eye The Hidden Dangers of Microsleep - Mohd Shahril, Abu Hanifah (UMPSA, 2024)
Imagine driving down the road, your eyes fixed on the stretch of asphalt ahead, when suddenly, you lose consciousness for just a few seconds. When you wake up, you realize with a jolt that your car has veered into another lane, dangerously close to causing an accident.